Rare Earth Elements Alter Redox Balance in Methylomicrobium alcaliphilum 20ZR - Akberdin, Ilya R.; Collins, David A.; Hamilton, Richard; Oshchepkov, Dmitry Y.; Shukla, Anil K.; Nicora, Carrie D.; Nakayasu, Ernesto S.; Adkins, Joshua N.; Kalyuzhnaya, Marina G. (Frontiers in Microbiology, 2018)
Background. Rare Earth Elements (REEs) control methanol utilization in both methane- and methanol-utilizing microbes. It has been established that the addition of REEs leads to the transcriptional repression of MxaFI-MeDH (a two-subunit methanol dehydrogenase, calcium-dependent) and the activation of XoxF-MeDH (a one-subunit methanol dehydrogenase, lanthanum-dependent). Both enzymes are pyrroquinoline quinone-dependent alcohol dehydrogenases and show significant homology; however, they display different kinetic properties and substrate specificities. This study investigates the impact of the MxaFI to XoxF switch on the behavior of metabolic networks at a global scale. Results. In this study we investigated the steady-state growth of Methylomicrobium alcaliphilum 20ZR in media containing calcium (Ca) or lanthanum (La, a REE element). We found that cells supplemented with La show a higher growth rate compared to Ca-cultures; however, the efficiency of carbon conversion, estimated as biomass yield, is higher in cells grown with Ca. Three complementary global-omics approaches—RNA-seq transcriptomics, proteomics, and metabolomics—were applied to investigate the mechanisms of improved growth vs carbon conversion. Cells grown with La showed the transcriptional activation of the xoxF gene, a homologue of the formaldehyde-activating enzyme (fae2), a putative transporter, genes for hemin-transport proteins, and nitrate reductase. In contrast, genes for mxaFI and associated cytochrome (mxaG) expression were downregulated. Proteomic profiling suggested additional adjustments of the metabolic network at the protein level, including carbon assimilation pathways, electron transport systems, and the tricarboxylic acid (TCA) cycle. Discord between gene expression and protein abundance changes points toward the possibility of post-transcriptional control of the related systems including key enzymes of the TCA cycle and a set of electron-transport carriers. Metabolomic data followed proteomics and showed the reduction of the ribulose-monophosphate (RuMP) pathway intermediates and the increase of the TCA cycle metabolites. Conclusions. Cells exposed to REEs display higher rates of growth but have lower carbon conversion efficiency compared to cells supplemented with Ca. The most plausible explanation for these physiological changes is an increased conversion of methanol into formate by XoxF-MeDH, which further stimulates methane oxidation but limits both the supply of reducing power and flux of formaldehyde into the RuMP pathway.